Influence of leadership emotional intelligence on employees' job satisfaction in the Malaysian public sector - Mohd Salleh, Lailawati; Kumar, Naresh; Abu Bakar, Nur Faezah (Malaysian Institute of Management, 2011)
The main purpose of this study was to determine the relationship between emotional intelligence and employees' job satisfaction in the Malaysian public sector. Result of this study found that leadership emotional intelligence has a moderate relationship with employee job satisfaction. The study also found that there is no significant difference on gender perception of their leader's emotional intelligence in that both male and female employees perceive their leaders as having a moderately high level of emotional intelligence. This shows that leaders in the public service are able to utilize their emotional intelligence to understand, manage and have a good relationship with their employees. More so, these leaders seem to be able to express positive emotions, thoughts and attitude towards their employees making their employees feel satisfied at the workplace.